Optimalisasi Keberdayaan Kelompok Pengerajin Bambu Khas Bangli dengan Penerapan Teknologi Inovasi Pemasaran dan Keuangan : Pengabdian - Nyoman Ayu Nila Dewi; I Ketut Widhi Adnyana; I Gusti Agung Vony Purnama; Luh Gede Cahya Maykernia Pratiwi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The beauty of Balinese artisans' handicrafts has long been known and sought after by local and foreign tourists. One of the handicraft products that has high cultural and economic value is keben, which is made of bamboo. However, keben craftsmen in Kayubihi Village, Bangli Regency, face various challenges such as limited access to technology, lack of marketing understanding, and low managerial skills. This community service activity aims to provide training and mentoring to keben craftsmen so that they can develop technical skills, understand effective marketing strategies, and improve business management. In addition, this activity also aims to raise awareness of the importance of preserving traditional crafts as part of cultural identity. Thus, it is hoped that craftsmen can increase their income and be ready to face the global era and international marketing. The results of the implementation of this community service activity are the achievement of 100% output for the e-commerce system, the Kayubihi Village web profile system, and the craftsmen's smart financial system. English language training has been carried out. So it can be concluded that the implementation of this community service activity has been achieved in accordance with the proposed target.